PENGARUH MANAJEMEN KONFLIK, KOMPENSASI DAN KEPEMIMPINAN TERHADAP KINERJA DENGAN KEPUASAN DAN KOMITMEN KERJA PADA CV. JAYA SENTOSA WILAYAH PAMEKASAN - Fadali Rahman; Ummi Wahyuni; Lailatus Saadah; Irsatus Solehah; Maulidi Insan Kamil (Jurnal Riset Multidisiplin Edukasi, 2025)
In a company, human resources are the main asset or the greatest investment a company owns. High-quality human resources are those who possess high competence and skills that can advance the company. A company will not run smoothly if it does not have quality human resources capable of carrying out the tasks assigned to them effectively. Research results show that Conflict Management affects employee performance in the company. When conflicts are managed properly, employees will feel more comfortable and motivated to work, which ultimately can improve their performance quality. In addition, Compensation affects employee performance. Providing fair and adequate compensation gives employees additional motivation to work better and improve their performance in performing administrative tasks within the company. Furthermore, choosing the right leadership style is very important for enhancing employee performance and creating a positive work culture. Leaders who can adjust their approach according to the situation and the team's needs will be more successful in achieving organizational goals.